Gut Microbiota-specific Profile Prior to Surgery for Predicting Type 2 Diabetes Remission in Patients Undergoing Sleeve Gastrectomy - Martínez-Montoro, José Ignacio; Sancho-Marín, Raquel; Garrido-Sánchez, Lourdes; Ocaña-Wilhelmi, Luis Tomás; Soler-Humanes, Rocío; Ruiz-Campos, Nerea; García-López, María José; Tinahones-Madueño, Francisco José; Gutiérrez-Repiso, Carolina (Springer, 2026)
Objective The predictive role of baseline gut microbiota in type 2 diabetes (T2D) remission after bariatric surgery remains unexplored. This study aimed to identify specific gut microbiota profiles prior to surgery associated with T2D remission fol- lowing sleeve gastrectomy (SG). Methods This was an observational study including participants with a body mass index (BMI) ≥ 40 kg/m2 and T2D who underwent SG, and had preoperative stool samples available. Gut microbiota was analayzed by 16 S rRNA sequencing. Par- ticipants were classified into remission and non-remission groups based on T2D status one year after SG. Results A total of forty-six participants were included. After adjusting for baseline confounders (i.e., age, HbA1c levels, T2D duration, and insulin treatment), preoperative gut microbiota diversity showed no statistically significant differences between groups, except for Pielou’s evenness index, which was significantly higher in the non-remission group (p = 0.01). ANCOM-BC2 analysis identified an enrichment in Fusicatenibacter, Holdemanella and Senegalimassilia in the non-remis- sion group, whereas Eggerthella, Flavonifractor, Ruminococcaceae g__Incertae Sedis and Ruminococcus gnavus group were enriched in the remission group. Furthermore, insulin treatment and the gut microbial taxa Ruminococcaceae g__Incer- tae Sedis, Fusicatenibacter, and Eggerthella emerged as potential predictors of T2D remission. Functional analysis using PICRUSt2 revealed increased carbohydrate metabolism pathways in the remission group. Conclusions Baseline gut microbiota composition may serve as an independent predictor of T2D remission in patients undergoing SG, and could become a potentially relevant biomarker, complementing other existing clinical predictors.
Keywords: Diabetes tipo 2; Type 2 diabetes; Sleeve gastrectomy; Gut microbiota; Diabetes remission